IMPLEMENTASI DATA MINING MENGGUNAKAN METODE APRIORI PADA TRANSAKSI PENJUALAN BARANG (STUDI KASUS DI CHORUS MINIMARKET) - Sihombing, Erika Silvia; Honggowibowo, Anton Setiawan; Nugraheny, Dwi (Compiler, 2012)
Minimarket chorus is where the sale of goods that have sales transaction data is large daily. Sale of transaction data in the Chorus Minimarket in store are usually only used as an archive only and not in the know what the benefits of a large sale of transaction data for later. The technique of data mining  can help  analyze of transactions  data large that is stored in database and can give benefits in the sale of items. Data mining process will be done is to extract  the knowledge from very large data amount of  and can then retrieve the information from these data. In this research, which used data mining with association rules is apriori method. Apriori method is used to find association patterns with a certain confidence level. Association rules used to know and give of information to find items is often be purchased together by customers. The data mining was be implemented by using Borland Delphi software and PostgreSQL databases to get information about the patterns of association rules from transaction data of item in the sale of Chorus Minimarket. Expected to application of data mining can provide benefits for the Chorus Minimarket later.